2017
DOI: 10.1080/16742834.2017.1368349
|View full text |Cite
|
Sign up to set email alerts
|

Observation of nocturnal low-level wind shear and particulate matter in urban Beijing using a Doppler wind lidar

Abstract: b center for excellence in regional Atmospheric environment, institute of Urban environment, chinese Academy of sciences, Xiamen, china; c college of earth science, University of the chinese Academy of sciences, Beijing, china; d chinese Academy of meteorological sciences, Beijing, china ABSTRACT A field experiment of nocturnal mountain wind and corresponding particulate matter (PM) evolution under weak synoptic forcing at five sites within urban Beijing was conducted using a moving Doppler wind lidar and a fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…In terms of the climate in Beijing, it typically belongs to a semi-humid continental climate in the north temperate zone, characterized by hot and humid summers due to the subsidence caused by the subtropical high, and cold, windy and dry winters which is mainly under the influence of the vast Siberian anticyclone [41][42][43]. Due to the huge amount of anthropogenic emission in the NCP (see Figure 1a), the atmospheric pollution (especially the PM 2.5 ) in Beijing has been intensively analyzed in recent years [38,39,41,44].…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the climate in Beijing, it typically belongs to a semi-humid continental climate in the north temperate zone, characterized by hot and humid summers due to the subsidence caused by the subtropical high, and cold, windy and dry winters which is mainly under the influence of the vast Siberian anticyclone [41][42][43]. Due to the huge amount of anthropogenic emission in the NCP (see Figure 1a), the atmospheric pollution (especially the PM 2.5 ) in Beijing has been intensively analyzed in recent years [38,39,41,44].…”
Section: Study Areamentioning
confidence: 99%
“…Among others, reanalysis data and model simulations were one of the most used approaches to analyze the variation of wind with different height in the lower troposphere and its impacts on air pollution, revealing a significant role of vertical wind shear (VWS, an important indicator of dynamically vertical mixing) in modulating particulate matter pollution [37,39,40]. In recent years, there has been a surge of interest in observational investigation of VWS in connection with atmospheric pollution, most of which are based on Doppler wind lidar [26,39]. However, the Doppler wind lidar has limited capability to offer vertically resolved wind observations under pretty clean or foggy conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Kondo et al (1989) revealed that the upslope and downslope motions under the influence of valley wind circulation could affect the daytime and nighttime energy budgets over the plain areas; Kuwagata et al (1990aKuwagata et al ( , 1990b pointed out that the heating rates in basin and inland plain are often larger than mountainous area and coastal plain under the influence of the compensating airflow of the upslope flow. Further studies based on the data with finer temporal and spatial resolution (e.g., wind-profiler measurements, meteorological tower) have advanced the knowledge of the effects on complex topography (e.g., Chen et al, 2017;Solanki et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the PBL climate should be regional dependent. In the NCP, previous works mostly focused on PBLs in several metropolises, for example, Beijing, Tianjin (Chen et al, 2017;Miao et al, 2017;Solanki et al, 2021), and only a few have studied the southern parts (e.g., Li et al, 2015;Zhu et al, 2018). Their spatial and temporal representativeness to the whole NCP was insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Other instruments i.e., Lidar Doppler and Terminal Doppler Weather Radar (TDWR) developed to detect wind shear is remote sensing-based tool (Chen et al, 2017;Chun et al, 2017;International Civil Aviation Organization, 2005;Nechaj et al, 2019;Shun and Chan, 2008;Thobois et al, 2019). Those Remote sensing instruments can detect wind shear at any height unlike LLWAS, but they are susceptible to the weather condition.…”
Section: Introductionmentioning
confidence: 99%